Theatre studies for professionalism: A call for secured future - Rijal, Shiva (Journal of Nepalese Studies, 2024)
This paper highlights the current course and challenges the modern and traditional theatre practitioners in Nepal have faced, and the steps that the stakeholders need to take to herald professionalism in the field. Any step taken by them needs to be guided by the objective of creating economically sustainable ground for the theatre profession. This paper also briefly mentions my findings about the way the stakeholders of the performance culture of Bali, Indonesia have managed to secure a market for their traditional dance and drama forms in the context of tourism of both domestic and international order. In the new political and economic context of Nepal, modern and traditional theatre practitioners need to link their arts and crafts with the urban market. For this, the practitioners need to have access to higher studies and learn to conduct research activities warranted by the market-oriented nature of modern theatre, the paper concludes.